2019
DOI: 10.2197/ipsjjip.27.643
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Robustness of Complex Networks against Random Node Removal

Abstract: It is widely known that scale-free networks are robust against random node removal, which is one of major interesting findings in network science. This suggests that, for instance, communication networks such as the Internet is robust against random node failures caused by breakdowns and/or malicious attacks if their network topologies are scale-free networks. Generally, the ratio of failed devices (e.g., routers) to operational devices is not extremely high. In this paper, we revisit the robustness of complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In our previous works, we have revealed that non-scale-free networks are robust when the node removal ratio is low, whereas scale-free networks are robust when the node removal ratio is high [8]. Also depending on the node removal ratio, the superiority of a network in terms of robustness is different.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous works, we have revealed that non-scale-free networks are robust when the node removal ratio is low, whereas scale-free networks are robust when the node removal ratio is high [8]. Also depending on the node removal ratio, the superiority of a network in terms of robustness is different.…”
Section: Introductionmentioning
confidence: 99%
“…Since the robustness is a multifaceted property of a network, several different metrics for network robustness -those from geometrical viewpoints (e.g., the size of the largest connected component, the average path length, and the efficiency) [3], [6], [7], [8], [9], [10] as well as spectral viewpoints (e.g., spectral radius, natural connectivity, and algebraic connectivity) [11], [12], [13], [14] -have been proposed in the literature.…”
Section: Introductionmentioning
confidence: 99%